From Challenges to Success: Supporting an Autism Spectrum Disorder Student's Final Project Journey in English Language Education - Wati, Mega; Subekti, Adaninggar Septi (JOLLT Journal of Languages and Language Teaching, 2026)
The study intends to explore the dynamics of a student with autism spectrum disorder in completing his product-based final project to graduate from an English education department and to identify the strategies that effectively facilitated this student to do so. It was conducted due to the scarcity of research studies reporting the step-by-step sucess journey of students with ASD in completing their degrees. It employed teacher action research using the final project advisor’s observation of the participant during all consultation sessions, her journal detailing her reflections on the participant's step-by-step progress and the participant's consultation log. The study was conducted from February 15 to February 2, 2024. Regarding the participant's dynamic in completing his final project, this study found that seventeen consultation meetings in one semester were needed to create the instructional video, while it took twenty consultation meetings in the next semester to guide him to write his final project report. The study found six strategies to help the participant complete his final project. These were allowing him to do one thing at a time, focusing on tasks within his competence, using repetition techniques for his comprehension, using oral feedback and tutorials instead of written ones, giving onsite consultation instead of online, and accompanying him in challenging tasks. Educators in other contexts may implement or adapt these strategies to facilitate the learning of students with ASD, taking into account both the similarities to and differences from the participant in the present study.